A time-step insensitive recurrent approach to analyze non-stationary random responses - Chen, Kui Fu; Zhang, Qiang; Zhang, Sen Wen (Computer Assisted Methods in Engineering and Science, 2009)
The recurrent approach constructed via the stochastic central difference (SCD) is a very fast method for analyzing non-stationary random responses. However, the computational results depend to a great extent upon the discrete time-step size. A new recurrent approach is proposed in this report. It is based on the theory of linear differential equations. Theoretical analysis shows that this algorithm is unconditionally stable for all damped systems. Two examples show that the proposed approach is not sensitive to the time-step.